Acute Effects of Whole-Body Vibration Warm-up on Leg and Vertical Stiffness During Running. Issue 9 (September 2021) - Paradisis, Giorgos P.; Pappas, Panagiotis; Dallas, Giorgos; Zacharogiannis, Elias; Rossi, Jérémy; Lapole, Thomas
Abstract : Abstract: Paradisis, GP, Pappas, P, Dallas, G, Zacharogiannis, E, Rossi, J, and Lapole, T. Acute effects of whole-body vibration warm-up on leg and vertical stiffness during running. J Strength Cond Res 35(9): 2433–2438, 2021—Although whole-body vibration (WBV) has been suggested as a suitable and efficient alternative to the classic warm-up routines, it is still unknown how this may impact running mechanics. Therefore, the aim of this study was to investigate the effect of a WBV warm-up procedure on lower-limb stiffness and other spatiotemporal variables during running at submaximal speed. Twenty-two males performed 30-second running bouts at 4.44 m·s −1 on a treadmill before and after a WBV and control warm-up protocols. The WBV protocol (vibration frequency: 50 Hz, peak-to-peak displacement: 4 mm) consisted of 10 sets of 30-second dynamic squatting exercises with 30-second rest periods within sets. Leg and vertical stiffness values were calculated using the spring mass model. The results indicated significant increases only after the WBV protocol for leg stiffness (3.4%), maximal ground reaction force (1.9%), and flight time (4.7%). Consequently, the WBV warm-up protocol produced a change in running mechanics, suggesting a shift toward a more aerial pattern. The functional significance of such WBV-induced changes needs further investigation to clearly determine whether it may influence running economy and peak velocity.